(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
With the surge of the Covid-19 pandemic, online sellers faced challenges particularly in managing their businesses amidst the uncertainties of the pandemic. This study aims to delve into the experiences of online sellers, focusing on the challenges and mitigating measures used by online sellers during pandemic. This qualitative study employs a phenomenological research design to explore the lived experiences of food online sellers during the Covid-19 pandemic. A total of five participants, consisting of food online sellers based in the local community, were selected through purposive sampling to provide rich and diverse insights into the challenges and mitigating measures associated with online selling during the pandemic. The study takes place in Tacloban City, a first-class, highly urbanized city in the Eastern Visayas region of the Philippines. Using semi-structured interviews food online sellers shared their experiences related to the challenges faced and the strategies employed in navigating the complexities of online selling during the pandemic. The findings of the study revealed eight emergent themes that encapsulate the informants' experiences, challenges, and coping strategies in food online selling during the pandemic. Specifically, three themes described their experiences: Low in Sales, Struggling in Buying Stocks, and Resorting to Online Business, which illustrate their initial difficulties and adaptive responses in transitioning to digital platforms. Regarding the challenges they encountered, three themes surfaced: Purchasing Ingredients, Dealing with Complaints and Addressing It Properly, and Relying on Delivery Drivers, pointing to supply chain issues, customer service concerns, and dependence on third-party logistics. Lastly, two themes represented the mitigating measures employed: SellerCustomer Relationship and Advertise the Product on Social Media, emphasizing the strategies informants used to maintain customer trust and boost visibility in a competitive online marketplace.